Influence of surface mass balance on the high-end sea-level commitment from the Antarctic Ice Sheet - Coulon, Violaine; Ann Kristin, Klose; Kittel, Christoph; Winkelmann, Ricarda; Pattyn, Frank (2022)
info:eu-repo/semantics/published